Moving (back) to the countryside: the role and interpretation of local traditions in the creation of sustainable architecture and new rural everyday life in Central Croatia - Lončar, Sanja, etnologinja (Array, 2013)
The work deals with contemporary phenomena connected with the rural space of Central Croatia and discusses the connection between local traditions and global trends, using as an example people who have decided to live in the countryside, living in accordance with the principles of sustainability. Based on a comparative ethnographic research conducted on several locations in central Croatia, the author discusses whether the 'return to the countryside' also involves a 'return to tradition'. She points to the differences and similarities between these examples, their connection to local or, on the other hand, global trends (environmental awareness, permaculture, off-grid life...). She focuses on activity and phenomena related to building houses using natural materials and living a new everyday village life. She analyses the mixing of local/traditional and environmental (in a broader sense) knowledge and skills. She also touches upon the methodological problems arising from the investigation, such as setting the limit of the investigation, selection of comparative examples, the use and applicability of the notions, etc.